1998
DOI: 10.1093/ndt/13.7.1652
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblasts and the progression of crescentic glomerulonephritis

Abstract: Abstractand interstitial collagen IV (r=0.588, P<0.01). In addition, the number of interstitial a-SMA+ cells and Background. The cellular and humoral factors involved in the pathogenesis of glomerulosclerosis and the extent of immunostain for collagen IV were positively correlated with the final serum creatinine (r= renal fibrosis following a crescentic glomerulonephritis have not been fully elucidated. Myofibroblasts and 0.517, P<0.05 and r=0.612, P<0.01 respectively) and partially predicted functional outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
45
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 3 publications
5
45
0
2
Order By: Relevance
“…However, although we show increased mRNA expression in the interstitial cells that was noticeably greater than in remnant kidneys, the contribution of this toward the total tTg pool is still minimal when compared with that of tubular cells (8,9). Therefore, although myofibroblasts may contribute significantly to the level of ECM components available for deposition during renal scarring (33)(34)(35), it is the perturbation of tTg production and its release by tubular cells that is likely to lead to the enhanced levels of ⑀(␥-glutamyl) lysine found in the ECM both in human as well as in experimental scarring (8,9). Of particular relevance is the observed close association and correlation between tTg and interstitial fibrosis, with an extremely high predictive value for the presence of tTg extracellular crosslink products and that of histologic abnormality.…”
Section: Discussionmentioning
confidence: 66%
“…However, although we show increased mRNA expression in the interstitial cells that was noticeably greater than in remnant kidneys, the contribution of this toward the total tTg pool is still minimal when compared with that of tubular cells (8,9). Therefore, although myofibroblasts may contribute significantly to the level of ECM components available for deposition during renal scarring (33)(34)(35), it is the perturbation of tTg production and its release by tubular cells that is likely to lead to the enhanced levels of ⑀(␥-glutamyl) lysine found in the ECM both in human as well as in experimental scarring (8,9). Of particular relevance is the observed close association and correlation between tTg and interstitial fibrosis, with an extremely high predictive value for the presence of tTg extracellular crosslink products and that of histologic abnormality.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies have reported that not only collagens type I and III but also collagen type IV, a basal membrane protein, is increased in patients with renal fibrosis such as crescentic glomerulonephritis. 19,20 Goumenos et al demonstrated that the site of synthesis of collagen III and IV appeared to be confined to fibroblasts in crescentic glomerulonephritis. 20 These findings suggest that renal fibroblasts play an important role in renal fibrosis through the synthesis of collagen types I, III, and IV.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have reported that interstitial mRNA expression of fiber-forming collagens (collagen types I and III) and collagen type IV, which is usually situated in cell basement membranes, is significantly increased in patients with renal fibrosis. 27,28 Interestingly, it was also demonstrated that the increased amounts of renal interstitial collagens were co-localized with fibroblasts. 28 These findings suggest that fibroblasts play a role in renal fibrosis through the synthesis of types I, III, and IV collagen.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Interestingly, it was also demonstrated that the increased amounts of renal interstitial collagens were co-localized with fibroblasts. 28 These findings suggest that fibroblasts play a role in renal fibrosis through the synthesis of types I, III, and IV collagen. In the present study, aldosterone Figure 3.…”
Section: Discussionmentioning
confidence: 99%